Lebanon : Report on Performance Under the Program Supported by Emergency Post-Conflict Assistance. (IMF Staff Country Reports; Country Report, 2007)
This report reviews Lebanon's performance under the program supported by emergency post-conflict assistance. The 2007 program is broadly on track. Despite a difficult political environment, all end-September targets were met, except for the monitorable action on raising gasoline excises. Fiscal revenues were stronger than expected. Owing to strong deposit inflows, the central bank accumulated international reserves at a faster pace than targeted. The end-December monitorable action on inviting expressions of interest to participate in the privatization of two mobile phone networks was effectively met in November.